2001
DOI: 10.1152/ajpcell.2001.280.6.c1455
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated receptor-2-mediated inhibition of ion transport in human bronchial epithelial cells

Abstract: A cytoprotective role for protease-activated receptor-2 (PAR2) has been suggested in a number of systems including the airway, and to this end, we have studied the role that PARs play in the regulation of airway ion transport, using cultures of normal human bronchial epithelial cells. PAR2 activators, added to the basolateral membrane, caused a transient, Ca2+-dependent increase in short-circuit current (I(sc)), followed by a sustained inhibition of amiloride-sensitive I(sc). These phases corresponded with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 26 publications
(47 reference statements)
5
39
0
Order By: Relevance
“…Similarly, PAR-2 regulates electrolyte transport in the airway epithelium, although there is no evidence for PAR-1 regulation of ion transport in the respiratory system (37,38). PAR-2 activators, when added to the basolateral, but not apical, surface of airway epithelial cells, regulate Na + absorption and Cl -secretion in a cytosolic Ca 2+ -dependent manner (37).…”
Section: Modulation Of Smooth Muscle Motility and Ion Transport By Prmentioning
confidence: 99%
“…Similarly, PAR-2 regulates electrolyte transport in the airway epithelium, although there is no evidence for PAR-1 regulation of ion transport in the respiratory system (37,38). PAR-2 activators, when added to the basolateral, but not apical, surface of airway epithelial cells, regulate Na + absorption and Cl -secretion in a cytosolic Ca 2+ -dependent manner (37).…”
Section: Modulation Of Smooth Muscle Motility and Ion Transport By Prmentioning
confidence: 99%
“…Second, Chokki and coworkers (55) showed that human airway trypsin-like protease, but not a PAR-2-activating peptide, induced MUC2 and MUC5AC gene expression in NCI-H292 cells. Finally, PAR-2 expression was restricted to the basolateral surface of airway epithelial cells (56), which would render it inaccessible to NE released by luminal neutrophils on the apical side of respiratory mucosa. Our recent unpublished data showed that while trypsin also induced MUC1 transcription, its activity was less than 10% of that generated by NE (I. Kuwahara, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…PAR2 (F2RL1) is one of the four known PARs and has been shown to play a role in secretion, smooth muscle contractility, neuromodulation, inflammation, fibrosis, angiogenesis and cancer metastasis (Bertog et al, 1999;Cocks et al, 1999;Danahay et al, 2001;Fiorucci et al, 2001;Hoogerwerf et al, 2001;Richard et al, 2001;Vergnolle et al, 2001;Frungieri et al, 2002;Hollenberg, 2002;Milia et al, 2002). We found that increased PAR2 expression enhanced, and reduced expression decreased, growth of RCC cell lines in vitro, suggesting that upregulation of TMSNB and PAR2 following VHL inactivation contributes to RCC tumorigenesis, although, we note that TMSNB and PAR2 were only upregulated in a proportion of primary RCC with VHL inactivation.…”
Section: Discussionmentioning
confidence: 99%